Hukou, Register of Households in China: Challenges of Internal Migration (1958-2018) [Hukou, Registro de Hogares en China: Desafíos de la Migración Interna (1958-2018)] - Norambuena-Carrasco, C; Duhalde-Valenzuela, B (Arturo Prat University, 2021)
Internal migration in China became a demographic problem in the early days of the People s Republic due to the inequality between rural and urban populations. To exercise more effective control, the government introduced the hukou system in 1958, which linked people to their place of birth, thus deepening the inequalities between the two areas. Sixty years after its implementation, this system has undergone various reforms, although its purpose remains the same. In the 21st century, the programme’s objective is to control migration from the rural sector to the city so as not to overpopulate the country’s megacities, maintaining the balance between internal migration and economic growth. This article offers a historical examination of institutional characteristics and a review of official documentation and the domestic press. The authors reflect on how this approach continues the institutionalised limitation of internal migration movements in the country, despite the social and economic transformations of China, and reforms to the system in the last decade. © Fabrizio Serra Editore, Pisa. Roma.